(untitled) (International Journal of Engineering and Computer Science, 2015)
In medical application the multimodal image fusion is an important tool. It has developed with the advent of various imaging modalities in medical imaging. It is mostly used for the medical diagnosis. In this proposal a novel fusion technique is proposed for the multi modal medical image based on the NSCT (non-sub sampled Contourlet transform). In this algorithm high frequency and low frequency components are fused by using fusion rules. In this project the two different fusion rules based on phase congruency and ‘averaging’ method is proposed. Finally the fused image is reconstructed by using the inverse NSCT with all coefficients. Simulation results show the proposed frame work provides the better and effective analysis of multimodal fusion. Simulation is done using MATLAB.